2008
DOI: 10.1111/j.1365-2966.2008.13520.x
|View full text |Cite
|
Sign up to set email alerts
|

Radio spectra and polarization properties of radio-loud broad absorption-line quasars

Abstract: We present multifrequency observations of a sample of 15 radio‐emitting broad absorption‐line quasars (BAL QSOs), covering a spectral range between 74 MHz and 43 GHz. They mostly display convex radio spectra which typically peak at about 1–5 GHz (in the observer's rest frame), flatten at MHz frequencies, probably due to synchrotron self‐absorption, and become steeper at high frequencies, i.e. ν≳ 20 GHz. Very Large Array (VLA) 22‐GHz maps (HPBW ∼80 mas) show unresolved or very compact sources, with linear proje… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
87
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(90 citation statements)
references
References 68 publications
3
87
0
Order By: Relevance
“…A significant difference between the distribution of α for BAL and non-BAL quasars has not been previously identified, but the sample sizes have typically been small (Fine et al 2011). Montenegro-Montes et al (2008) did identify a difference in the α distributions of their samples-however when they restricted their analysis to include only compact sources the difference disappeared. Additionally, BAL quasars with polar rather than equatorial outflows have likely been identified via short timescale variation in radio flux (Zhou et al 2006;Ghosh & Punsly 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant difference between the distribution of α for BAL and non-BAL quasars has not been previously identified, but the sample sizes have typically been small (Fine et al 2011). Montenegro-Montes et al (2008) did identify a difference in the α distributions of their samples-however when they restricted their analysis to include only compact sources the difference disappeared. Additionally, BAL quasars with polar rather than equatorial outflows have likely been identified via short timescale variation in radio flux (Zhou et al 2006;Ghosh & Punsly 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Becker et al (2000) find that only about 10% of BAL quasars show extended structure at 5 ′′ resolution, compared to about 50% of normal quasars. In a sample of 15 BAL quasars, Montenegro-Montes et al (2008) find that all of them are compact at FIRST resolutions, and the majority remain compact at around 80 mas resolution. Even very long baseline interferometry (VLBI) observations, which has down to milli-arcsecond resolution, often show BAL quasars as compact objects (Doi et al 2009, Jiang & Wang 2008, Kunert-Bajraszewska et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Instrumental polarisation from the Lovell and Effelsberg telescopes is known to be small (see e.g. Montenegro-Montes et al 2008;Gould & Lyne 1998), Notes. Given are the integration time (T int ), catalogue value for dispersion measure (DM, Hobbs et al 2004), the pulse period (P, determined from regular timing observations from the Lovell telescope at Jodrell Bank Observatory), the LOFAR observation ID and the number of bins across the pulse profile (N bin for each of the pulsars observed).…”
Section: Observationsmentioning
confidence: 99%
“…Becker et al (2000) first used the radio emission spectral index to derive the jet orientation of BAL QSOs, and noted that this can lie in wide range of possible angles. After these works, different authors presented detailed studies about larger samples of radio-loud BAL QSOs, from which they reported a variety of possible orientations for the outflow, but also a variety of possible morphologies and ages for the radio source (Montenegro-Montes et al 2008;DiPompeo et al 2011;Bruni et al 2012Bruni et al , 2013). This does not suggest a scenario that would be clearly referable to one of the proposed models.…”
Section: Introductionmentioning
confidence: 99%